New H i observations of KK 69. Is KK 69 a dwarf galaxy in transition? - Saponara, Juliana (2020)
We present new HI data of the dwarf galaxy KK 69, obtained with the Giant Metrewave Radio Telescope (GMRT) with a signal-to-noise ratio almost double previous observations. We carried out a Gaussian spectral decomposition and stacking methods to identify the cold neutral medium (CNM) and the warm neutral medium (WNM) of the HI gas. We found that 30% of the total HI gas, which corresponds to a mass of ∼107 M☉, is in the CNM phase. The distribution of the HI in KK 69 is not symmetric. Our GMRT HI intensity map of KK 69 overlaid onto a Hubble Space Telescope image reveals an offset of ∼4 kpc between the HI high-density region and the stellar body, indicating it may be a dwarf transitional galaxy. The offset, along with the potential truncation of the HI body, are evidence of interaction with the central group spiral galaxy NGC 2683, indicating the HI gas is being stripped from KK 69. Additionally, we detected extended HI emission of a dwarf galaxy member of the group as well as a possible new galaxy located near the north-eastern part of the NGC 2683 HI disk.